External heated humidification during non-invasive ventilation set up: results from a pilot cross-over clinical trial. Issue 5 (21st May 2020) - Mandal, Swapna; Ramsay, Michelle; Suh, Eui-Sik; Harding, Rachel; Thompson, April; Douiri, Abdel; Moxham, John; Murphy, Patrick Brian; Hart, Nicholas
Patient comfort is important in ensuring adherence to domiciliary non-invasive ventilation (NIV). Oronasal dryness is often reported with NIV use [1], but the use of heated humidification in clinical practice is not uniform [2]. As there are limited data to currently guide clinical practice, we investigated the effect of external heated humidification on neural respiratory drive (NRD), patient–ventilator asynchrony (PVA), patient-reported outcomes, ventilator performance and adherence in a pilot randomised crossover trial in patients with chronic respiratory failure during NIV set up. Short-term heated humidification has limited effect on physiological and clinical outcomes during non-invasive ventilation set up http://bit.ly/31cFfGt